Isolation of an endogenous type C virus related to the infectious primate type C viruses from the Asian rodent Vandeleuria oleracea. - Callahan, R (1979)
A tissue culture line derived from the Asian rodent Vandeleuria oleracea has been shown to release an infectious, xenotropic type C virus. The virus-associated reverse transcriptase (RNA-dependent DNA nucleotidyltransferase) and the major internal protein p30 are immunologically related to the respective proteins of the woolly monkey-gibbon ape group of infectious primate viruses. By these criteria the V. oleracea viral isolate is similar to the murine type C-I class of endogenous retroviruses and has been designated Vand C-I. Nucleic acid homology studies show that V. oleracea cellular DNA shares similar levels of homology with DNA from members of the Mus and Rattus genera and lower levels of homology with other rodent genera. The Vand C-I viral genome is present in V. oleracea cellular DNA in multiple copies, and partially related sequences can be detected in other rodent genera. These results support the conclusion that the Vand C-I viral genome is genetically transmitted in V. oleracea and that the type C-I class of endogenous retroviral genes has been highly conserved during evolution.